2022
DOI: 10.3389/fvets.2022.908479
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Molecular Evidence of Coxiella burnetii in Dromedary Camels of Pakistan

Abstract: Coxiellosis is a zoonosis in animals caused by Coxiella burnetii. A cross-sectional study was conducted on 920 (591 female and 329 male) randomly selected camels (Camelus dromedarius) of different age groups from 13 districts representative of the three different ecological zones in the Province Punjab, Pakistan to determine the prevalence and associated risk factors of coxiellosis. The blood samples were collected and tested for anti-C. burnetti antibodies using indirect multispecies ELISA. Real-time PCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Variation in Q fever seroprevalence between bovines and additional animal species in Pakistan could also be expected based on the research elsewhere. Hussain et al, for example, detected anti-C. burnetii antibodies in 288 of 920 camels sampled in Pakistan (31.3%, 95% CI 28.3–34.4%) 57 , suggesting higher seroprevalence in this species than in the cattle/buffalo population sampled in the current study (25.45%, 95% CI 21.52–29.79). Work has also been done in this region to suggest that C. burnetii is widespread outside of its living hosts, being detectable by DNA analysis in 47 of 2,425 soil samples taken by Shabbir et al 1 , though with soils testing positive at a notably lower rate than animals (i.e.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Variation in Q fever seroprevalence between bovines and additional animal species in Pakistan could also be expected based on the research elsewhere. Hussain et al, for example, detected anti-C. burnetii antibodies in 288 of 920 camels sampled in Pakistan (31.3%, 95% CI 28.3–34.4%) 57 , suggesting higher seroprevalence in this species than in the cattle/buffalo population sampled in the current study (25.45%, 95% CI 21.52–29.79). Work has also been done in this region to suggest that C. burnetii is widespread outside of its living hosts, being detectable by DNA analysis in 47 of 2,425 soil samples taken by Shabbir et al 1 , though with soils testing positive at a notably lower rate than animals (i.e.…”
Section: Discussionmentioning
confidence: 42%
“…According to the limited available literature, the seroprevalence of Q fever in Pakistan ranges from 4.6 to 40% in all livestock species, and from 10.2 to 26.8% in humans 55 , 56 . The rates of premature births and weak calves are particularly high in certain districts, including those selected for study in the current work 57 which was designed to fully assess Q fever seroprevalence and associated factors in large ruminants on livestock farms in Punjab, Pakistan. In estimating the seroprevalence of coxiellosis in seven districts not previously targeted in preceding research, this study provides essential information for policy makers and concerned authorities to implement prevention and control strategies against coxiellosis in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Blood-feeding arthropods are serious pests of worldwide distribution, including the camel tick, Hyalomma dromedarii (Koch, 1844); cattle tick, Rhipicephalus (Boophilus) annulatus, formerly Boophilus annulatus (Say, 1821), (Acari: Ixodidae); the adult cattle louse fly, Hippobosca maculata Leach (Diptera: Hippoboscidae); and the shortnosed cattle louse, Haematopinus eurysternus (Nitzsch, 1818), (Psocodea: Haematopinidae). Haematophagous pests cause dermal damage to be grazing animals, leading to severe economic loss because of blood loss, irritation, general stress, damaged skin and hide, retarded growth, weight loss, depression of the immune system, decreased meat and milk production, and transmission of life-threatening diseases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies [ 29 , 31 , 32 ], even higher prevalence (approximately 51%–62%) was observed in Saudi camels. Similarly, camels have a high prevalence rate of 66% in Egypt [ 33 ], 29% in Iran [ 25 ], 71.2% in Algeria [ 34 ], 80% in Chad [ 35 ], 44% in Tunisia [ 36 ], 31.3% in Pakistan [ 26 , 37 ] and Eastern Ethiopia [ 38 ], as well as in 100% of nomadic camels. This high prevalence may be attributed to poor hygiene and management conditions in which animals live, where crowding and lack of disinfection lead to the transmission of infection, as well as direct exposure to contaminated dust and heat, as well as an appropriate environment for the breeding of ticks that transmit the disease through saliva or feces.…”
Section: Resultsmentioning
confidence: 99%
“…According to our findings, camels may be a source of C. burnetii in Saudi Arabia and may play a role in the spread of Q fever to people in this region of the world [ 18 ]. In addition, Q fever has been frequently reported in camels from other parts of Asia and North Africa [ 25 , 37 , 39 ]. In addition, the genetic susceptibility of camels to C. burnetii infection [ 30 , 34 ] or predilections of tick vectors to camels may have contributed to this phenomenon.…”
Section: Resultsmentioning
confidence: 99%